THE IMPACT OF INFOGRAPHICS ON LEARNING OUTCOMES IN DESIGN EDUCATION - Teo , Pei Kian; Tan , Si Min; Megawati, Citra Dewi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Recently, the exclusive focus on student engagement in education has been undeniable, at least following the disruption around people doing things differently because of the Covid-19 pandemic. Various visualization tools, especially infographics, have been widely used to increase student engagement due to their ability to convey information in an accessible and visual format. This research highlights the impact of infographics on students’ engagement and interest as a part of learning experience through graphic design education and has been conducted accordingly. Using a systematic literature review, the research takes a look at both the advantages and difficulties of including infographics within design programs. This paper reviews evidence from a variety of academic studies to evaluate the effectiveness of infographics on student engagement and educational achievement. Furthermore, a meta-analysis of the chosen publications summarizes the statistics regarding their efficiency in terms of engaging the participants within the design programme. Findings of the study provide important implications for educators, instructional designers, and curriculum developers regarding the implementation of infographics in teaching practice as strategies to improve student learning. The paper will conclude with recommendations to integrate infographics in curriculum design in design education.